Dark CO2 fixation in temperate beech and pine forest soils. (February 2022) - Akinyede, Rachael; Taubert, Martin; Schrumpf, Marion; Trumbore, Susan; Küsel, Kirsten
Abstract: Soils are the largest terrestrial organic carbon pool and the largest terrestrial source of atmospheric CO2 . Non-phototrophic CO2 fixation by microbes re-fixes and recycles CO2 respired in soils. Our previous study showed that in temperate deciduous forest soil profiles, rates of dark CO2 fixation were proportional to microbial biomass, irrespective of soil depth. However, the amount and quality of organic matter entering different soil depths vary for different temperate forest types and these influence microbial communities with unknown consequences for CO2 fixation rates. To test whether differences in the amount and quality of SOC caused by tree species affect dark CO2 fixation rates with depth, we conducted a study using acidic soils from two forest plots from the Schorfheide-Chorin Exploratory, Germany. These soils, dominated by either beech (deciduous) or pine (coniferous) tree stands differ in their SOC content and quality. We traced the incorporation of 2% (v:v) 13 C–CO2 label into microbial biomass and estimated the CO2 fixation rates relative to microbial biomass carbon content (in μg C g MBC −1 d −1 ) across the soil profiles. The rates of dark CO2 fixation per g MBC were similar across the beech soil profiles, but significantly lower in the pine soils at the B2 and BC horizons, suggesting that while dark CO2 fixation rates are linked to MBC in deciduous forest soils, other factors influence dark CO2 fixation rates in coniferous forest soils. The pine subsoils had low SOC content and quality, with a microbial community enriched with heterotrophic fermenters like Chloroflexi that are predicted to have a lower potential for heterotrophic CO2 fixation compared to the other dominant bacteria phyla. In contrast, the beech soil profiles, characterized by higher SOC inputs, featured higher fractions of copiotrophs like Proteobacteria, Acidobacteria, and Actinobacteria predicted to have high heterotrophic CO2 fixation potential. We thus speculate that in contrast to the beech soils, lower SOC inputs in the pine subsoils affected the community composition, leading to lower CO2 fixation rates. We further made comparisons to soils dominated by mixed deciduous trees and featuring a higher MBC and SOC content. Over this range of temperate forest soils, CO2 fixation rates were highest in the mixed deciduous forest soils, with MBC and Shannon index (used as a proxy parameter for community composition) showing the strongest correlations with the varying CO2 fixation rates. Our study suggests that predictions of dark CO2 fixation rates need to consider tree-species specific or site-specific conditions, as these may alter root carbon inputs and affect microbial community composition and their metabolic CO2 fixation potentials in soil. Highlights: Dark CO2 fixation rates correlate with MBC in beech soil profiles. In pine subsoils, CO2 fixation rates per gram MBC are lower than in beech soils. Lower rates in pine subsoils reflect distinct subsoil communities and SOC inputs. Comparing 3 temperate forests, microbial communities control CO2 fixation rates. SOC & vegetation effects on the community explain their control on fixation rates.